ON THE ESTABLISHMENT OF THE INFORMATION SYSTEM OF DOMESTIC DISSERTATION RESEARCH IN A SCIENTIFIC SPECIALTY 14.02.01 «HYGIENE»: STATUS AND SOLVING - V. I. Evdokimov; A. N. Ruth (Радиационная гигиена)
There have been provided an analysis of the digitized full-text abstracts and dissertations on the official websites of institutions with dissertation councils on hygiene, in the digital libraries of the Russian State Library (RSL) and the National Library of Russia (NLR) and the website of the Higher Attestation Commission at the Ministry of Education. An array was formed of 1446 theses on the specialty 14.02.01 (old code – 14.00.07) «Hygiene» for 2000–2012. Doctoral theses comprised 19.8 % – significantly more than cumulative biological and medical theses (14.8 %) for the same period inRussia. Polynomial trend with a coefficient of determination (R2 = 0.73) with statistical significance indicates a decrease in the number of theses. Every year inRussiadissertation councils on hygiene received (111 ± 9) theses. It is established that in 76.9 % of abstracts are digitized in NLR and 63.7 % in RSL. Digitized documents can be accessed in the halls of the library for free, and in a mode of remote access – for a fee. Measures to optimize dissertation documents digitizing by librarians are described, as well as to seek opportunities to create a unified information system of dissertation research in Russia in the Scientific Electronic Library within the reference-analytical system Science Index for dissertation councils, free subscription of national research libraries to digital full-text databases of abstracts and dissertations and integration of Russian scientists in the international scientific community.